(untitled) (Research, Society and Development, 2021)
The economic and environmental impacts related with fossil fuels dependency have encouraged the source of renewable energy sources. In remotes areas is common to use the diesel-generators for electric power generation. So, the biodiesel proves to be a great alternative for the electric generators. In this study was realized the energy and exergetic analysis of an engine-generator group diesel cycle subject to 5 alternating charges operating with 5 mixtures of fuel at different percentages between diesel and canola biodiesel. It was realized 25 essays in the engine-generator group to establish the specific fuel consumption, exhaust gas temperature, fuel energy, thermal efficiency, exhaust gas energy, heat transfer losses, fuel exergies, exergetic efficiency, exhaust gas exergy, destroyed exergy and the exergy of the heat transfer losses. It was found by increases in charge the specific fuel consumption lowers and the pure diesel showed the lowest consumption. At 2000 W and 2500 W the pure biodiesel has the best thermal efficiency. The pure biodiesel at 2000 W and 2500 W has the best exergetic efficiency and the blends with the biggest biodiesel percent showed the lowest exergy destruction.